Autogenetic changes of vegetation in the Ingul River Valley (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Autogenetic changes of ve getation in the Ingul River Valley have been investigated. We located 12 transverse ecological gradients among different climatic conditions. We analyzed features of the natural dynamics of vegetation in the Ingul River Valley based on its serial developme nt. We highlight 8 series of vegetation which are combined into 3 groups based on the type of humidification conditions xerosere, mesosere and hydrosere. The first one is the most widespread in the Ingul River Valley, its communities occupy 80% of the to tal area. In this group four pioneer stages were detected: on carbonates in the downstream of the river (lithosere), on silicates in the middle part of the river (lithosere), on sands (psammosere) and on loesses (xerogeosere). Each of them can be considere d as a separate alliance of vegetation Potentillo arenariae Linion czerniaevii (vegetation on limestone outcrops), Poo bulbosae Stipion graniticolae (vegetation on granitic outcrops), Festucion beckeri (psammophitic vegetation), Tanaceto millefolii Galat ellion villosae (true steppe vegetation)vegetation). Mesosere communities have less distribution (not more than 5% of total area). Two initial stages were detected: alluvial mesosere and hygrolithosere. The first one combines alluvial shrub vegetation of the Salicete a p urpureae class, that are common on the upper part of the river. The second one includes chasmophytic vegetation on the granitic outcrops of the Ukrainian crystal shield. Communities of hydrarch changes (hydrosere) are common along the riversides. These coenoses allocate 15% of the total area. They are represented by eutrophic hydrosere and halosere. Pioneer stage of the eutrophic hydrosere is a true aquatic vegetation of Lemnetea and Potametea classes. Halosere is represented by two pioneer stages com munities of Salicornietum prostratae and Crypsietum aculeatae.
Keywords: syndynamics, succession, communities, series, autogenesis, endogenetic changes.